A Literature Review: The Impact of Religious Education Implementation on Mental Health and Psychological Well-Being of Elementary School Children - jumal muraidin (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2025)
Religious education at the elementary school level plays a crucial role in shaping children’s character, moral values, and mental balance from an early age. This stage of education is a critical period for emotional, social, and cognitive development, where the internalization of spiritual values becomes essential to foster empathy, self-awareness, and emotional well-being. However, in practice, religious education often focuses primarily on cognitive and doctrinal aspects, which limits its impact on students’ psychological and emotional growth. This study aims to analyze the influence of religious education on children’s mental health and psychological well-being through a descriptive-comparative literature review method. Data were collected from various academic journals, scientific studies, and research findings published between 2020 and 2025, focusing on the relationship between spirituality and elementary education. The analysis reveals that contextual, reflective, and interactive religious education has a significant positive impact on improving students’ spiritual well-being, emotional regulation, and psychological resilience. Reflective learning approaches that encourage dialogue and empathy help students internalize spiritual values through real-life experiences, resulting in balanced intellectual, emotional, and spiritual development. Empirical findings from elementary schools in Sorong City also indicate that reflective and experience-based religious learning enhances children’s empathy, self-control, and emotional stability. Nevertheless, challenges persist, including the dominance of traditional teaching models centered on memorization and the growing influence of digital culture on children’s behavior. The study concludes that religious education must evolve into a collaborative, experiential, and spiritually grounded pedagogical model to effectively support children’s mental health, foster moral maturity, and promote sustainable psychological well-being. Keywords: Religious Education, Mental Health, Psychological Well-Being